(3BdjGJ JaYjd GdfXGe GdSjGSj hGdGLJeGYj ddeQCIs - (3YHO GdaJGM eMeO(B, (3YUGes ((3GdbGgQI (B:s (3eDSSI WjHI ddfTQ hGdJhRjY(B,s, 2023)
(3GdhLhO GdSjGSj ddeQCI, deMI Yf GdGfLGRGJ hGdJMOjGJ aj eLGd JMbjb GdeSGhGI Hjf GdLfSjf hJecjf GdeQCI, deMI Mhd HQGeL GdJecjf GdSjGSj ddeQCI , GdJejjR GdeROhL, OhQ GdeQCI aj YedjI UfY GdbQGQ hJhdj GdeSDhdjGJ , OhQ GdCMRGH GdSjGSjI aj JaYjd OhQ GdeQCI GdSjGSj, GdETcGdjGJ hGdLOd Mhd GdJecjf GdSjGSj ddeQCI , eYhbGJ GdeTGQcI GdSjGSjI ddeQCI aj GdYGde GdESdGej, eYhbGJ GdeTGQcI GdSjGSjI aj ddeQCI aj GdYGde GdESdGej, GdeQCI hGdMQGc GdGLJeGYj HGdbWGY GdZjQ QSej, Mbhb GdeQCI GdGbJUGOjI hGdGLJeGYjI hGdKbGajI , JLQHjI GdeQCI aj GdbjGOI dOi GdSdWI GdadSWjfjI , BdjGJ JaYjd GdeTGQcI GdSjGSjI ddeQCI, JNUjU MUU ddfSGA(B((3GdchJG(B) (3, GdeQCI hGdeLGd GdSjGSj aj VhA GdOSJhQ GdeQJbH, GdeQCI hGdOSJhQ Hjf JcQjS GdhGbY hGdJZjjQ Gdeecf(B. s
(3GdeQGLY U(B.299s
Keywords: (3GdSjGSI (B- (3GdeQCI (B- (3GdhWf GdYQHjs; (3GdeQCI (B- (3GdQYGjI GdELJeGYjI s